A Modified Peak Load Method Based on the Two-Parameter Model in Concrete Fracture - Ince, Ragip (ISRES Publishing, 2025)
The experimental studies on fracture mechanics of concrete until the 1970s revealed that classical linear elastic fracture mechanics (LEFM) was invalid for cementitious materials such as mortar and concrete. This inapplicability of LEFM is due to the existence of an inelastic zone with large-scale and full cracks in front of the crack tip in concrete. This so-called fracture process zone is ignored by LEFM. For this reason, several investigators have developed nonlinear fracture mechanics approaches to characterize failure of concrete structures. According to the two-parameter model (TPM) in concrete fracture, a free crack propagates unstably whenever the stress intensity factor and the crack tip opening displacement are equal to their threshold values, such as Mode I fracture toughness and critical crack tip opening displacement, respectively. This methodology derives fracture parameters from one of two experimental techniques: the compliance method and the peak load method. In the compliance method, fracture parameters are ascertained from the correlation between the load and the crack mouth opening displacement of beams, utilizing closed-loop testing apparatus, while the peak-load method, which does not necessitate complex testing apparatus, is more straightforward than the compliance method for determining fracture parameters within TPM. In this study, a modified peak load method based on an optimization procedure was proposed to determine fracture parameters of TPM instead of the statistical procedure based on the peak load method. © 2025 Published by ISRES Publishing: www.isres.org.
5th International Conference on Basic Sciences and Technology, ICBAST 2025 -- 28 August 2025 through 31 August 2025 -- Budapest -- 344359
Keywords: Beam test; Concrete; Fracture mechanics; Semi-circular bending test; Two-parameter model